The China Shock and the Nationalist Backlash against Globalization: Attitudinal Evidence from the British Household Panel Survey - Philipp Harms; Nils Steiner (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
While recent studies have examined how economic shocks arising from trade competition affect voting results at the aggregate level, we know little about the individual-level mechanisms that bring such effects about. In this contribution, we use long-term individual-level panel data to study the effects of local exposure to import competition on political attitudes. We specifically hypothesize that losing out from trade causes a broad nationalist backlash against globalization, i.e. a decrease in support for international cooperation and a rise in nationalist sentiments. In addition, we explore effects on political disaffection and economic policy preferences. Drawing on the British Household Panel Study (1991-2008), we study intra-individual change in individuals' political attitudes to allow for a clean identification of causal effects. We focus on the local consequences of the 'China shock' and measure the exposure of British NUTS3-regions to the growth in imports from China as a function of their initial sectoral employment structure. We first verify that the 'China shock' had significant negative effects on individual incomes. Our results on the effects on political attitudes are broadly supportive of the nationalist backlash-thesis. Individuals residing in regions with a stronger "China shock" turn more critical of EU membership as well as of international cooperation in general and show an increase in nationalist sentiment. In contrast, we find no evidence for an effect on positions on economic left-right issues. Our study speaks to the debate about the sources behind the anti-globalization backlash observed in Western democracies and shows how citizen's attitudes towards issues that are primarily seen as cultural, like national identity, are endogenous to the distributional consequences of international trade.
Keywords: F16; F66; F68; 330